LATERAL PUSH ELEMENT - KARLSSON, Daniel (2020)
The disclosed subject matter generally relates to a lateral push element adapted to be arranged inside a hollow beam structure disposed on a lateral side of a vehicle. The lateral push element is configured to provide a lateral load path in the event of a partial overlap collision involving the vehicle. Some hollow beam structures on the lateral sides of the vehicle are often heavily deformed when the incoming barrier hit the hollow beam structures. The hollow beam structures are not in themselves able to transfer a lateral force. The space inside the hollow beam structures may thus be utilized for enabling additional lateral forces in the event of a partial overlap collision. The present disclosure provides a lateral push element adapted to be arranged inside the hollow beam structure disposed on a lateral side of a vehicle, and that is configured to provide a lateral load path in the event of a partial overlap collision involving the vehicle.